The bad consequences of suspicion in hadiths of the Ahl al-Bayt, peace be upon them (Journal of Imam Al-Kadhim College, 2025)
The research, entitled “The Bad Consequences of Suspicion in the Hadiths of the Ahl al-Bayt, peace be upon them,” deals with the definition of suspicion and doubt from a linguistic and technical perspective, while clarifying the difference between them The research presented texts and narrations from the Ahl al-Bayt, peace be upon them, that warned against doubt and suspicion, demonstrating their emphasis on the danger of surrendering to doubtsThe study revealed that the most dangerous consequences of suspicion and doubt include the corruption of social relations, the lack of trust among Muslims, the weakening of faith, and the whisperings of the soul, all of which lead to the spread of strife and conflict. The study also addressed the most prominent therapeutic methods for preventing suspicion and doubt Such as good intentions, investigating before making judgments, and relying on nourishing the heart with sincere faith and piety, in accordance with the directives of the Noble Prophetic Sunnah, and the necessity of promoting Islamic values ​​in societies.
Keywords: (suspicion, consequence, hadiths); suspicion; consequence; hadiths